REPRESENTASI BUDAYA POPULAR DALAM ILUSTRASI KARTUN YESUS KRISTUS DI SITUS PENYEDIA GAMBAR ONLINE - Palit, Rene Arthur; Sulaiman, Naniwati (Serat Rupa: Journal of Design, 2022)
Bible stories use illustrations in Christian religious education, especially for Sunday School children. Currently, there are various variations of Jesus cartoon illustrations available on the internet. So Sunday school teachers can freely choose a variety of cartoons. In addition to helping the teacher, there are several problems with the cartoon illustration. The cartoon style facilitates humor and satire through distortion and exaggeration of form. This opens up opportunities to present counterproductive visualizations of Jesus comparing the Bible. So that visually the cartoon can actually contain messages that are different or even contrary to the principles of the Christian faith being taught. Behind the cartoon illustration of Jesus, there are certain perspectives, values and beliefs. This study aims to reveal the messages conveyed by popular culture through the cartoon style of the Jesus illustrations. For data collection, the authors conducted visual observations, literature studies, and analysis of the visual elements of the Jesus cartoon illustrations. This is done by referring to the context of the popular culture it represents. The conclusion of the study reveals various popular culture messages contained in certain Jesus cartoon illustrations. These messages are generally not in harmony with the character of Jesus Christ that the Bible teaches. The results of the research are expected to help Christian religious educators to choose the right illustrations. Especially for Sunday school teachers in choosing a cartoon illustration of Jesus Christ.